The Japan-Multimodal Intervention Trial for Prevention of Dementia PRIME Tamba (J-MINT PRIME Tamba): Study protocol of a randomised controlled multi-domain intervention trial. (January 2023) - Kumagai, Ryoko; Osaki, Tohmi; Oki, Yutaro; Murata, Shunsuke; Uchida, Kazuaki; Encho, Haruhi; Ono, Rei; Kowa, Hisatomo
Highlights: The J-MINT PRIME Tamba study is an 18-month multimodal intervention RCT. Cognitively normal older people living in the community are targeted. Interventions include lifestyle management and physical and cognitive training. The primary outcome is change in the cognitive composite score. This study will benefit the development of dementia prevention measures in Japan. Abstract: The Japan-Multimodal Intervention Trial for Prevention of Dementia PRIME Tamba (J-MINT PRIME Tamba) is a randomised controlled trial to prevent cognitive decline in community-dwelling cognitively ordinary older people at risk of dementia. Participants are aged 65–85 years living in a rural area in Japan, aware of very mild decline in cognitive function or abilities of activities of daily living, have at least one vascular risk (e.g. hypertension or diabetes), and have a Mini-Mental State Examination score of 24 or higher. Approximately 200 participants are randomly divided into two groups, with the intervention group receiving a multi-modal intervention, including lifestyle-related disease management, physical exercise, cognitive training, and nutritional counselling, over 18 months. The primary outcome is change in the composite score of seven neuropsychological tests, including the Free and Cued Selective Reminding Test, Logical Memory I and II subsets of the Wechsler Memory Scale-Revised, and Digit Symbol Substitution Test of the Wechsler Adult Intelligence Scale. In addition, changes in a wide range of other parameters such as physical function, blood test results, sleep, and frailty are also analysed as secondary outcomes. We believe that this study's results will contribute significantly to the development of dementia prevention measures in Japan. Clinical trial registration number: UMIN000041938